WAJAH POLITIK AFGHANISTAN ERA 1933 ? 2002 DALAM THE KITE RUNNER KARYA KHALED HOSSEINI - Ahmad Fanani (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2013)
Abstract 'Kite Runner' tells the story of Afghanistan in 1970 to 2002. As like other countries, Afghanistan has a long and complicated history, but Afghanistan gets international attention since a coup in 1973. This article reveals how well the author, Khaled Hosseini, described the political realities in Afghanistan since 1933 to 2002. Though the main theme of this novel is about the friendship between Amir, of the tribe of the Pashtun majority, and Hassan, the Hazara ethnic minority, but this novel also tells a lot about the culture and politics of Afghanistan. In short, although 'The Kite Runner' tells the story of friendship, but it is also good enough to be used as a reference for those who want to know about the state of Afghanistan, not just about politics, but also the state of nature and culture.